Histopathological evaluation of dental follicles associated with impacted third molars - Rogério Vera Cruz Ferro Marques; Daniele Meira Conde Marques; Fernanda Ferreira Lopes; Leonardo Victor Galvão-Moreira; Maria Carmen Fontoura Nogueira da Cruz (Universidade Estadual de Campinas, 2018)
Aim: To histologically evaluate dental follicles of impacted third molars with no radiographic evidence of pathology. Methods: We carried out both a quantitative and qualitative analysis of pericoronal follicles removed from impacted third molars and investigated the association with clinical data. The sample included 36 extracted dental follicles of impacted third molars, obtained from 28 patients, which presented with no radiographic evidence of pathologies. Results: None of the follicles analyzed showed any pathological entity. The epithelial lining was observed in 61.1% of samples, being identified as reduced enamel epithelium. We found a significant relation between the the presence of inflammatory infiltrate and the group aged over 21 years (64.3%; p<0.05). Conclusions: Considering the absence of pathological lesions, we suggest that impacted third molars should only be extracted in young-aged individuals due to specific pathologies or indications.